Moderne Frauen, die Neue Welt und der alte Kontinent: Käthe Schirmacher reist im Netzwerk der Frauenbewegung - Gehmacher, Johanna (Österreichische Zeitschrift für Geschichtswissenschaften, 2011)
Taking the example of the German feminist activist Käthe Schirmacher (1865–1930), the article explores the significance of travel practices for political movements and argues for greater dialogue between travel studies and research on social movements. It demonstrates the growing mobility within European and North American women’s movements at the end of the 19th century and argues that the internationalization of political and social movements at the turn of the century generated a new type of travelling activist. These activists not only built formal and informal networks and enabled the transfer of programs and perspectives, but also served as travelling role models with whom local activists could identify. In the 1890s, the young Käthe Schirmacher, who was born in Danzig, had studied in Paris, worked as a teacher in England and had obtained her doctorate (as one of the first German women) in Zurich, became an important protagonist in the emerging international network of the radical women’s movement. Having to support herself, she made a profession out of her feminist activism. As a journalist and author of books on women’s movement issues she regularly travelled around Europe as a speaker for local feminist organisations – a practice which was politically effective as well as rewarding. The article explores how Schirmacher developed this practice after her return from the international women’s congress that was held on the occasion of the World’s Fair in Chicago 1893. It analyses the textual strategies as well as the racist undertones by which she portrayed the US women’s movement and its much-admired protagonists, and invented herself as a “modern woman” who cooperated with these feminist heroes.